Propofol-induced frontal aEEG changes in children during deep procedural sedation - Paul, Luisa; Tschiedel, Eva; Daniels, Anna; Brensing, Pia; Joist, Carolina A.; Joist, Constantin M.; Greve, Sandra; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Bruns, Nora (Frontiers in neurology, 2025)
BackgroundAmplitude-integrated EEG (aEEG) is an important neuromonitoring tool in paediatric critical care, but effects of agents used for procedural sedation on aEEG patterns are not understood. The aim of this study was to explore the correlation between deep procedural sedation and modifications in aEEG amplitudes in children without cerebral pathologies.MethodsIn this prospective observational study, 165 children aged 6 months to 17.9 years undergoing procedural sedation with propofol and premedication with midazolam were monitored using frontal aEEG (Fp1, Fp2, FpZ according to the 10-20 system). Sedation depth was assessed using the Comfort Score (CS).ResultsThe median patient age was 8.8 years (interquartile range 3.9-14.0), with a median procedure duration of 19 min. A total of 1,464 paired observations of CS and amplitude measurements were analyzed. The lower amplitude showed a moderate negative correlation with CS (deeper sedation associated with higher amplitude), increasing by 1.4 μV per one-point decrease in CS with variations between age groups. The upper amplitude remained largely unchanged during deep sedation, whereas the bandwidth narrowed. The lower amplitude increased from baseline by a median of 6.5 μV (37.9% relative increase), with variations across age groups.ConclusionDeep procedural sedation with propofol primarily affects the lower amplitude of frontal aEEG, with age-dependent variations. These findings advance the understanding of propofol-induced aEEG changes in neurologically healthy children, which may enhance bedside aEEG interpretation in paediatric patients.
Gesehen am 14.11.2025